Database System for Land Suitability Analysis and Cultivation Information System of National Valuable Fruits - . Santosa; Bambang Pramudya; Moeljarno Djojomartono; Kudang B. Seminar; . Strisno; Slamet Susanto (Jurnal Keteknikan Pertanian, 2000)
A database system has been developed to prodict land suitability and cultivation information of national valuable fruits. The database system covers commodity of fruits database, agro-ecological database, and salaccia and mango information database. "A computer program for determining the best of land suitability was designed based on fruits database and agroecological database.